Efficacy of Progesterone Receptor Antagonist for Treatment of Pyometra in Bitches - Chandrakar, Upasana; Tiwari, Rajendra P.; Poyam, Mahesh R.; Mishra, Girish K. (Indian Journal of Veterinary Sciences and Biotechnology, 2021)
The present study aimed to assess the efficacy of Progesterone Receptor Antagonist for Treatment of Pyometra in Bitches. The present research work was carried out on a total of 12 bitches diagnosed with pyometra. The animals were randomly assigned to two treatment protocols, with 6 animals in each group. In Group I, bitches were administered only with supportive therapies, i.e. fluid therapy, cloprostenol, and ceftriaxone. In Group II, bitches were administered with progesterone receptor antagonist (mifepristone) and supportive fluid therapy as in Gr-I. The physiological, hematological, and biochemical parameters were evaluated on days 0, 4th, and 8th of treatment. The recovery rate of treated bitches was assessed by ultrasonography post-treatment. There was a significant increase in the mean PCV and a decrease in leucocyte count in group II on day 8. After treatment, the mean serum globulin and creatinine level reduction was significant (p<0.05) in group II than group I. The mean serum ALT concentration in bitches with pyometra in different groups pre-treatment, during, and post-treatment were within the normal physiological range (10-94 U/L). The mean concentration of serum ALP decreased significantly (p<0.05) in both groups on day 8. The ultrasound examination on day 8 post-treatment revealed a reduction in uterine lumen, the thickness of the uterine wall, and decreased echogenicity indicative of treatment response in both groups. Bitches treated with progesterone receptor antagonist (mifepristone, Group-II) showed higher recovery (100 vs. 50%) and lower recurrence (17 vs. 67%) than Group I. From the present findings, it could be concluded that progesterone receptor antagonist proves to be a safe and efficient drug for the treatment of pyometra in bitches.